Role conflict, satisfaction, and performance in administrative staff at public universities: The role of optimism and sex differences - Pedro Antonio Díaz-Fúnez; Francisco Gabriel Martín-Martín; Ana Martínez-Díaz; Carmen Salvador-Ferrer; Chiara Consiglio; Miguel Ángel Mañas-Rodríguez (PLoS ONE, 2025)
Background This study addresses a critical gap in the literature by examining how optimism can moderate the effects of role conflict specifically among administrative staff at public universities. Role conflict is a prevalent challenge for these workers, who must navigate the demands of various groups with opposing needs, such as the university’s governing body, different professors and researchers, students, and suppliers. This situation can be a stressor that depletes their resources. Previous research has shown the negative impact of role conflict on job satisfaction and performance; however, few studies analyze this relationship in administrative employees at public universities considering their individual characteristics. One individual factor that has been shown to mitigate the negative effects of role conflict is employees’ optimism, but it is necessary to analyze whether this effect is also observed in this uniquely characterized work context and across both sexes (women/men). Objectives The purpose of this study is to verify whether role conflict has a negative impact on job satisfaction and perceived performance among administrative employees. Additionally, it aims to investigate whether employees’ optimism moderates the negative effects of role conflict on job satisfaction and performance. Moreover, this study will explore whether the effects of role conflict and optimism vary based on the employee’s sex (women/men), considering potential differences in how these factors influence their experiences and outcomes in the workplace. Design and Methods Data were collected from 334 employees with administrative and customer service roles at a public university (172 men and 162 women). This sample size provides sufficient statistical power to detect significant effects, allows for reliable subgroup analysis by gender, and aligns with typical sample sizes in organizational and psychological research. Results The results confirm that role conflict has a significantly negative influence on performance through job satisfaction (mediation effect), although only in the men group. Moreover, this process is moderated by optimism (Men: IE =.0733, SE =.028, 95% CI BC from.0210 to.1296; Women: IE =.0312, SE =.046, 95% CI BC from -.0660 to.1146). Conclusions It is concluded that role conflict negatively affects the perception of one’s own performance among administrative employees. However, while in the men group this relationship is mediated by job satisfaction and moderated by optimism, in women, role conflict directly affects performance. This difference may be due to distinct coping strategies and emotional responses to work demands between men and women, which influence how job satisfaction impacts perceived performance. These findings suggest that interventions aimed at increasing optimism and other personal resources may be particularly effective in mitigating the negative effects of role conflict, especially in men. Nonetheless, in the case of women, it is important to further investigate other potential individual factors that may moderate role conflict, as well as implement strategies that directly reduce stress sources in the workplace.